Riflessioni sul processo di nullità matrimoniale nel contesto della delibazione in Italia (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. L'art. 60 del Decreto generale sul matrimonio canonico della CEI e l’obbligo di delibare - 3. La fase dell’indagine pregiudiziale e quella introduttiva - 4. La fase istruttoria e quella discussoria - 5. La fase decisoria - 5.1. Della redazione della sentenza - 5.2. Dell’interferenza delle questioni patrimoniali - 6. Conclusioni.Reflections on marriage nullity proceedings in the context of the Italian exequatur procedureABSTRACT: The obligation to request the exequatur of the ecclesiastical sentence of marriage nullity, foreseen by the art. 60 of the General decree on the canonical matrimony of the CEI, constitutes in Italy a legal duty for the faithful who determines, for judges and lawyers, a corresponding moral duty (but which for lawyers can also become legal, under the professional mandate) of collaboration, during the various prejudicial and judicial phases of the canonical proceedings, in acquiring and making available all the useful elements in view of a exequatur procedure.
Keywords: Delibazione sentenze ecclesiastiche